Implementation of Peer Tutoring in Reading and Memorizing Qur'anic Verses for Students of Class IX SMP Negeri 32 Semarang - Amri, Muhammad Farizal (Journal of Education and Religious Studies, 2024)
This research aims to explore the effectiveness of the peer tutoring in improving the skills of reading and memorising Qur'anic verses among students of SMP Negeri 32 Semarang. peer tutoring allows students who are more proficient in reading the Qur'an to act as tutors for their peers who need guidance, thus creating a collaborative and supportive learning atmosphere. This study used a qualitative approach with a case study method, where data were collected through interviews, observations, and document analyses. The results showed that the application of the peer tutoring improved students' interaction, confidence, and skills in reading and memorising Qur'anic verses. Observations showed that 99% of students achieved good or very good grades in these skills, with an increase in activeness and mutual respect between students. The method proved effective, especially in time-limited learning conditions, and provided positive experiences for students, both as tutors and tutees.